Potential Role of NEU1 in Hepatocellular Carcinoma: A Study Based on Comprehensive Bioinformatical Analysis - Wu, Zhulin; He, Li; Yang, Lina; Fang, Xuehong; Peng, Lisheng (Frontiers in Molecular Biosciences, 2021)
Background: Aberrant expression of NEU1 has been identified in many malignancies. Nevertheless, the clinical significance of NEU1 in hepatocellular carcinoma (HCC) has not been fully elucidated. Methods: In our study, multiple databases, including ONCOMINE, The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), International Cancer Genome Consortium (ICGC), Cancer Cell Line Encyclopedia (CCLE), Human Protein Atlas (HPA), Kaplan-Meier (KM) plotter, MethSurv, Gene Expression Profiling Interactive Analysis (GEPIA), and Metascape, etc., were utilized to investigate the expression, prognostic value, and function of NEU1 in HCC. Results: ONCOMINE, GEO, and TCGA analyses revealed that NEU1 was more highly expressed in HCC compared to normal tissues. Additionally, the mRNA and protein expression levels of NEU1 were increased in liver cancer cell lines and HCC tissues, respectively. Moreover, a trend toward increased NEU1 expression with advanced stage or grade was found. Furthermore, higher mRNA expression of NEU1 was found to be remarkably correlated with worse survival in HCC patients, and multivariate Cox analysis indicated that high mRNA expression of NEU1 was an independent prognostic factor for poor prognosis of HCC patients. Also, 21 methylated CpGs were found to be significantly related to HCC prognosis. Besides, functional enrichment analyses indicated that high NEU1 expression group had lower levels of B cells, CD8+ T cells, NK cells, and T helper cells, etc. than the low NEU1 expression group, and NEU1 may regulate a variety of tumor-related proteins and pathways, including lysosome, spliceosome, mTOR signaling pathway and so on. Conclusion: High expression level of NEU1 was positively correlated with unfavorable prognosis of HCC patients, which may be related to the regulation of cancer-associated pathways and the inhibition of immune function by NEU1. Thus, NEU1 could be used as a potential prognostic biomarker and target for HCC.